Modelling Deep Learning Neural Networks For Pneumonia Detection - et. al., M Rama Bai, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
A Contagious Disease Called Pneumonia Is The Single Largest Infectious Respiratory Disease That Is As Common As Cold. Pneumonia Is A Form Of An Acute Respiratory Infection That Affects The Lungs. The Lungs Of The Victim Are Filled With Pus And Fluid, Which Results In Painful Breathing And Also Reduces The Intake Of Oxygen. According To The World Health Organisation (Who), Pneumonia Accounts For 15% Of All Deaths Of Children Under 5 Years Old, Killing 808,694 Children In 2017. The Success Of The Deep Neural Networks In The Field Of Image Classification Has Aided Medical Professionals By Improving Their Decision Making. Convolutional Neural Networks, A Branch Of Deep Neural Networks Came Into The Spotlight Due To The Ability To Classify Diseases Based On Medical Images. In This Work, We Study The Application Of Cnn's In The Context Of Pneumonia Detection. We Tactically Determine The Optimal Architecture For Classifying The X-Ray Images To Indicate The Presence Of Pneumonia.